Assessment in art therapy - Gilroy, Andrea, 1949-; Tipple, Robin; Brown, Christopher (London : Routledge, 2012)
'Assessment in Art Therapy gives a unique insight into the diverse contemporary practices that constitute assessment in art therapy, providing an overview of the different approaches employed in Britain and America today. This professional handbook comprises three main sections. Sitting beside explores the discursive and the relational in art therapy assessments with adults and children in different settings. Snapshots from the field presents a series of short, practice-based reports which describe art therapists working in private practice, secure settings and community mental health centres. A more distant calculation consists of chapters that describe the development and use of different kinds of art-based assessment procedures developed on both sides of the Atlantic, as well as different kinds of research about art therapy assessment. Both students and practitioners alike will benefit from the wealth of experience presented in this book, which demonstrates how art therapists think about assessment; the difficulties that arise in art therapy assessment and the importance of developing the theory and practice of art therapy assessment, whilst taking into account the changing demands of systems and institutions'--
'Assessment in Art Therapy gives a unique insight into the diverse contemporary practices that constitute assessment in art therapy, providing an overview of the different approaches employed in Britain and America today. This professional handbook comprises three main sections. Sitting beside explores the discursive and the relational in art therapy assessments with adults and children in different settings. Snapshots from the field presents a series of short, practice-based reports which describe art therapists working in private practice, secure settings and community mental health centres. A more distant calculation consists of chapters that describe the development and use of different kinds of art-based assessment procedures developed on both sides of the Atlantic, as well as different kinds of research about art therapy assessment. Both students and practitioners alike will benefit from the wealth of experience presented in this book, which demonstrates how art therapists think about assessment; the difficulties that arise in art therapy assessment and the importance of developing the theory and practice of art therapy assessment, whilst taking into account the changing demands of systems and institutions'--
Keywords: Art therapy -- Evaluation